Understanding the Patterns of Antibiotic Susceptibility of Bacteria Causing Urinary Tract Infection in West Bengal, India - Saha, Sunayana; Nayak, Sridhara; Bhattacharyya, Indrani; Saha, Suman; Mandal, Amit; Chakraborty, Subhanil; Bhattacharyya, Rabindranath; Chakraborty, Ranadhir; Franco, Octavio L.; Mandal, Santi M.; Basak, Amit (Frontiers in Microbiology, 2014)
Urinary tract infection (UTI) is one of the most common infectious diseases at the community level. In order to assess the adequacy of empirical therapy, the susceptibility of antibiotics and resistance pattern of bacteria responsible for UTI in West Bengal, India, were evaluated throughout the period of 2008-2013. The infection reports belonging to all age groups and both sexes were considered. E. coli was the most abundant uropathogen with a prevalence rate of 67.1%, followed by Klebsiella spp. (22%) and Pseudomonas spp. (6%). Penicillin was least effective against UTI-causing E. coli and maximum susceptibility was recorded for the drugs belonging to fourth generation cephalosporins. Other abundant uropathogens, Klebsiella spp., were maximally resistant to broad-spectrum penicillin, followed by aminoglycosides and third generation cephalosporin. The antibiotic resistance pattern of two principal UTI pathogens, E. coli and Klebsiella spp. in West Bengal, appears in general to be similar to that found in other parts of the Globe. Higher than 50% resistance were observed for broad-spectrum penicillin. Fourth generation cephalosporin and macrolides seems to be the choice of drug in treating UTIs in Eastern India. Furthermore, improved maintenance of infection incident logs is needed in Eastern Indian hospitals in order to facilitate regular surveillance of the occurrence of antibiotic resistance patterns, since such levels continue to change.